Application of Digital Marketing to MSMEs Bangka Dumpling Noodle Mr.Ong - Lady, Lady; Wijaya, Calvin; Dyfan; Noviani, Metta; Raymond; Yendiarti (Manager : Jurnal Ilmu Manajemen, 2023)
Ruko Botania in Batam Center is an area where the author's activities are carried out. It should be noted that MSMEs in Indonesia have a very important impact on the role of the economy, Mr.Ong's Bangka Pangsit Noodle MSME is a business engaged in the culinary food sector. This UMKM was opened in 2010 at Botania Garden. The concept of digital marketing originates from the internet and search engines on websites. Creating an Instagram account for the promotion of Mie Pangsit Ayam Bangka Mr.Ong in the form of a product photo that has been designed to include Instagram and a Whatsapp number, and a Facebook contact as well as a Google Maps link which will make it easier for consumers if they want to visit the place of business directly. the instastory feature is also used so that the account's followers can find out the latest info from Mie Pangsit Bangka Mr.Ong, namely @miepangsitbangka.mrong. The purpose of implementing digital marketing for Mr. Ong's Bangka Pangsit Noodle business is so that this business can be better known by the people of Batam. Apart from that, creating social media accounts is also free. Social media will make it easier to interact with customers